Ejective and preventative: the IllustrisTNG black hole feedback and its effects on the thermodynamics of the gas within and around galaxies. Issue 1 (31st August 2020) - Zinger, Elad; Pillepich, Annalisa; Nelson, Dylan; Weinberger, Rainer; Pakmor, Rüdiger; Springel, Volker; Hernquist, Lars; Marinacci, Federico; Vogelsberger, Mark
ABSTRACT: Supermassive black holes (SMBHs) that reside at the centres of galaxies can inject vast amounts of energy into the surrounding gas and are thought to be a viable mechanism to quench star formation in massive galaxies. Here, we study the 10^9-12.5 M_ stellar mass central galaxy population of the IllustrisTNG simulation, specifically the TNG100 and TNG300 volumes at z = 0, and show how the three components – SMBH, galaxy, and circumgalactic medium (CGM) – are interconnected in their evolution. We find that gas entropy is a sensitive diagnostic of feedback injection. In particular, we demonstrate how the onset of the low-accretion black hole (BH) feedback mode, realized in the IllustrisTNG model as a kinetic, BH-driven wind, leads not only to star formation quenching at stellar masses 10^10.5 M_ but also to a change in thermodynamic properties of the (non-star-forming) gas, both within the galaxy and beyond. The IllustrisTNG kinetic feedback from SMBHs increases the average gas entropy, within the galaxy and in the CGM, lengthening typical gas cooling times from 10\!-\!100 Myr to 1\!-\!10 Gyr, effectively ceasing ongoing star formation and inhibiting radiative cooling and future gas accretion. In practice, the same active galactic nucleus (AGN) feedback channel is simultaneously 'ejective' and 'preventative' and leaves an imprint on the temperature, density, entropy, and cooling times also in the outer reaches of the gas halo, up to distances of several hundred kiloparsecs. In the IllustrisTNG model, a long-lasting quenching state can occur for a heterogeneous CGM, whereby the hot and dilute CGM gas of quiescent galaxies contains regions of low-entropy gas with short cooling times.